The Quality Management System in Kyrgyzstan: Achievements and Challenges - Ryskulova, Chynarkul (International Higher Education, 2023)
Kyrgyzstan implemented a new system of quality assurance through independent accreditation agencies in 2016. Poor management of the accreditation process, insufficient faculty training, and misunderstanding of the essence of quality culture present serious challenges. The absence of institutional research structures and specialized professional accreditation agencies are the main issues.